Pelatihan Kelompok Sadar Wisata (Pokdarwis) Melalui Kegiatan Tata Kelola Destinasi Pariwisata Di Kabupaten Jember - Juhanda; Hidayatullah, Syarif; Sandy, Syah Riza Octavy (Journal Of Humanities Community Empowerment, 2023)
Jember Regency has many tourist destinations, so it has around 20 million tourist visits. The potential tourist attractions in the Jember Regency area are quite large, including; natural, cultural, culinary and innovative economic tourism that spreads in 248 villages, but this opportunity has not been used by the local community as a tourism interest. The purpose of this training is to provide POKDARWIS with an understanding of the role, obligations and benefits for tourism boosters in rural environments, Pokdarwis is given direction and insight to explore and develop tourism capacity by conducting training on tourism destination management. This study utilizes qualitative descriptive methods that describe directly and clearly. It is hoped that this training will have insight into good management of tourist destinations and can share their knowledge with the community in the tourist environment. Therefore, the formation of community understanding to increase tourism capacity in rural environments